Stable overexpression of mutated PTEN in Chinese hamster ovary cells enhances their performance and therapeutic antibody production. Issue 9 (19th June 2021) - Zhou, Qin; Zhang, Yujie; Lu, Xiaoxiang; Wang, Chang; Pei, Xinxin; Lu, Yafang; Cao, Cheng; Xu, Changzhi; Zhang, Buchang
Abstract: Chinese hamster ovary (CHO) cells with a high viable cell density (VCD), resilience to culture stress, and the capacity to continuously express recombinant proteins are highly desirable. Phosphatase and tension homology deleted on chromosome ten (PTEN) functions as a key negative regulator of the PI3K/Akt signaling pathway, mediating cell growth and survival. Its oncogenic mutant endows cells with an enhanced proliferation rate and resistance to death. In this study, the role of oncogenic PTEN C124S or G129E on the performance of CHO‐K1 and CHO‐IgG cells was investigated. Our results showed that CHO‐K1 cells stably expressing PTEN C124S or G129E exhibited enhanced proliferation, reduced apoptosis rate, and increased transient expression of therapeutic antibodies compared to the control cells. Moreover, the stable overexpression of PTEN C124S or G129E endowed CHO‐IgG cells with higher cell viability, VCD, and antibody titers (yield increased by approximately 0.77‐fold) in the fed‐batch culture process and enhanced their performance in response to the addition of sodium lactate. Moreover, the engineering of mutated PTEN in CHO‐IgG cells did not alter antibody quality. Collectively, our data suggest that mutated PTEN is a potential target for improving the manufacture of therapeutic antibodies. Abstract : The overexpression of functional genes is a common strategy used in CHO cell engineering. In this study, the authors demonstrate that CHO‐IgG cells stable expressing PTEN C124S or G129E exhibited enhanced cell viability, VCD, and antibody titers in the fed‐batch culture process by activating the PI3K/Akt signaling pathway. This work is the potential basis for improving the manufacture of therapeutic antibodies.